Easy Web page creation - Millhollon, Mary (Microsoft, 2001)
Demonstrates professional Web writing, design, and information-organizing techniques while explaining how to plan, create, post, and maintain Web sites using such Microsoft applications as Windows Notepad, Word, and FrontPage.